The role of the 3′-UTR of the chemokine receptor CCR2 and hnRNPA0 in regulating mRNA stability and subcellular distribution in human CD4+ T cells - Yukselten, Yunus; Wishah, Hanan; Wang, Lingyun; Sutton, Richard E. (Frontiers in Immunology, 2025)
IntroductionCCR2, a chemokine receptor critical for immune cell migration, inflammation, and HIV infection, is regulated by poorly understood mechanisms.MethodsThis study investigated the unusually long CCR2 3’-UTR’s role in post-transcriptional regulation.ResultsThe full-length 3′-UTR significantly inhibited reporter gene expression in primary CD4+ T cells and macrophages, likely mediated by RNA binding proteins (RBPs). HnRNPA0, was shown to bind directly to this region and influence CCR2 levels. When the RBP binding sites were mutagenized or the 3′- UTR removed using CRISPR-Cas9 and gRNAs, CCR2 mRNA and protein levels significantly increased. Cell fractionation experiments confirmed that these changes occurred in both the nucleus and cytoplasm. To directly test mRNA stability, we used a-amanitin and found that removing the 3′-UTR nearly doubled the half-life of CCR2 mRNA. Finally, pseudotyping studies revealed CCR2 functions as an HIV co-receptor at ~10% efficiency compared to CCR5.DiscussionThese results show that the CCR2 3′-UTR plays an important role in post-transcriptional regulation and may provide a novel approach to regulating CCR2 activity in inflammatory or infectious diseases.